From nature deficit to outdoor exploration: curriculum for sustainability in Vermont's public schools. Issue 3 (3rd July 2017) - Silverman, Jonathan; Corneau, Nicole
ABSTRACT: Children today are spending less time than ever outdoors, contributing to a culture of environmental apathy and separation from the natural world. In the growing field of environmental education, teachers are challenged to introduce the outdoors into their curriculum. In Vermont, some public school teachers have successfully implemented environmental education into their practice in a variety of interesting ways. This paper analyzes a series of teacher interviews and observations in Vermont public schools to identify successful strategies and pedagogies being utilized for environmental education. Several common themes emerged from this study, including place-based education, hands-on exploration, and free choice learning.